PEMĀTESEN ATĀĒQNŌHKAKAN: A DIVERGENT SUBSET OF THE LIFE IS SACRED PROJECT - (:unkn) unknown (My University, 2024)
Murder-suicide constitutes a particularly tragic form of violence that has a powerful effect on communities. However, it remains severely understudied. No research to date has examined the incidence of death by murder-suicide events within American Indian/Alaskan Native (AI/AN) communities, despite AI/AN persons being at a disproportionately high risk for suicide and other forms of violence such as stalking, trafficking, physical violence and psychological aggression by intimate partners, and sexual violence. This project represents a subset of a larger Menominee Indian Tribe of Wisconsin (MITW)/University of Wisconsin-Milwaukee (UWM) partnership to address suicide mitigation within the Menominee tribal community. This project’s purpose was to explore both individual and community risk and protective factors along with the impact of Historical Trauma on this type of violence. Using qualitative methodology, this project employed the Extended Case Method (ECM) to conduct Life Reviews (also known as psychological autopsy) for each incidence of completed or attempted death by murder-suicide between 2007 and 2021. Examination of record data and completion of interviews with eight participants contributed to a deeper understanding of both individual and contextual risk and resiliency factors unique to this form of violence. Participants shared factors across all domains identified within the developed Indigenous Ecological Model (Rouse, unpublished), spoke to the impact of Historical Trauma on the MITW, and identified needed community resources. Moreover, the participants expressed the significance of their own involvement in the project. Further discussion of the project’s findings, theoretical considerations, need for use of an ecological model, limitations and future directions are considered.
Keywords: American Indian/Alaska Native; Historical Trauma; Murder-Suicide; Qualitative